2008
DOI: 10.1073/pnas.0802218105
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 blockade inhibits the induction of myelin antigen-specific Th17 cells and Th1 cells in experimental autoimmune encephalomyelitis

Abstract: autoimmunity ͉ multiple sclerosis ͉ T cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
260
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(284 citation statements)
references
References 33 publications
13
260
2
Order By: Relevance
“…In Arid5a −/− mice, both serum levels of IL-6 and TNF-α were dramatically inhibited after EAE induction. A previous report showed that anti-IL-6 antibody inhibited both IL-6 and TNF-α levels in serum after EAE induction (21). Therefore, it is conceivable that chronic elevation of IL-6 level affects TNF-α level more than acute augmentation of IL-6 level by LPS does in vivo.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Arid5a −/− mice, both serum levels of IL-6 and TNF-α were dramatically inhibited after EAE induction. A previous report showed that anti-IL-6 antibody inhibited both IL-6 and TNF-α levels in serum after EAE induction (21). Therefore, it is conceivable that chronic elevation of IL-6 level affects TNF-α level more than acute augmentation of IL-6 level by LPS does in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…4B). Inhibition of induction of IL-17-producing T helper cells (T H 17 cells) by reduction of IL-6 level in vivo contributes to suppression of EAE (21). Therefore, we examined whether Arid5a deficiency affects the number of IL-17-producing T cells of CD4 + population after EAE induction.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in various autoimmunity models, such as experimental autoimmune encephalomyelitis (36), uveoretinitis (37), CIA (2,38), and glucose-6-phosphate isomerase-induced arthritis (39), showed that anti-IL-6R antibody treatment suppressed antigen-specific Th17 cell differentiation. In our study, Th17 cell frequencies were not significantly different between tocilizumab responders and nonresponders, and no significant changes were observed throughout the course of CIA in MR16-1-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-6, along with TGF-β, induces Th17 and inhibits TGF-β-induced Treg-cell differentiation [34], and IL-6 deficient mice are EAE resistant [35]. Application of IL-6 receptor mAb [36] ameliorates inflammation in several autoimmune diseases including EAE [37,38]. Also, TNF-α is likely involved in Th17 differentiation [39].…”
Section: Discussionmentioning
confidence: 99%